Nitrous oxide emissions from wetland soil amended with two types of cattle manure - Masaka, Johnson; Nyamangara, Justice; Wuta, Menas (Springer, 2021)
Purpose The implications of increased applications of high quality cattle manure to agricultural systems in Africa on N2O emissions are still only partially understood.